REPRÉSENTATIONS SOCIALES ET RAPPORT À L’ÉCRIT : ANALYSE DES MÉMOIRES DE MASTER ET THÈSES DE DOCTORAT - Manel Khendriche; Imane Ouahib (Studii de gramatică contrastivă)
In this article, we propose to analyze students' perceptions regarding the writing of dissertations, particularly master’s dissertations and doctoral theses, with reference to Abric's (1989)central core theory. The primary aim of this research is to understand students' relationship with academic writing and to identify the obstacles they encounter when completing their dissertations. More specifically, we aim to identify their perceptions of dissertation writing and examine how these perceptions influence their engagement with academic writing. To this end, we conducted a survey of individuals meeting specific criteria. The participants, selected based on their academic level and involvement in dissertation writing, include students and/or faculty members at Algerian universities. They have completed or are currently working on a master’s dissertation or doctoral thesis in the Humanities, with a focus on Didactics, Literature, and Linguistic Sciences. The data collected werea nalyzed using both quantitative and qualitative approaches to identify the challenges faced by participants. Findings from this study reveal a lack of academic training and significant writing challenges, which heighten the sense of insecurity associated with writing. Consequently, respondents' relationship with academic writing appears complex and characterized by difficulties. This research underscores the urgent need to improve academic training in writing methodology and to provide sustained guidance throughout students’ academic journeys, in order to facilitate the writing of final dissertations.